2014
DOI: 10.1074/jbc.m114.554162
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and Metabolic Stress Stimulate Multisite Serine/Threonine Phosphorylation of Insulin Receptor Substrate 1 and Inhibit Tyrosine Phosphorylation

Abstract: Background: Metabolic stresses, including hyperinsulinemia, promote insulin resistance. Results: Monoclonal antibodies raised against Ser(P)/Thr(P) residues in IRS1 were used to quantify phosphorylation in response to insulin or agents that model metabolic stress. Conclusion: Similar IRS1 Ser(P)/Thr(P) residues are increased by insulin or metabolic stress, and some correlate significantly with reduced IRS1 tyrosine phosphorylation. Significance: Metabolic stress co-opts insulin-dependent IRS1 phosphorylation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 91 publications
(110 reference statements)
3
74
0
1
Order By: Relevance
“…These observations provide further strong support for a causal negative impact of mitochondrial ROS production on AKTdependent insulin signaling, which agrees with previous observations (1)(2)(3)(4)(5). UnAG effects were associated with enhanced inhibitory IRS-1 S312 phosphorylation; this seemingly paradoxical observation is, however, consistent with reports of IRS-1 S312 phosphorylation as a physiological negative feedback modulation following downstream signaling activation (31).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…These observations provide further strong support for a causal negative impact of mitochondrial ROS production on AKTdependent insulin signaling, which agrees with previous observations (1)(2)(3)(4)(5). UnAG effects were associated with enhanced inhibitory IRS-1 S312 phosphorylation; this seemingly paradoxical observation is, however, consistent with reports of IRS-1 S312 phosphorylation as a physiological negative feedback modulation following downstream signaling activation (31).…”
Section: Discussionsupporting
confidence: 69%
“…These effects were further associated with enhanced IRS-1 S312 phosphorylation (Fig. 3B), an mTORC-dependent negative feedback mechanism and marker for enhanced insulin signaling (31). To determine whether activating IRS-1 phosphorylations were also enhanced, we measured pIRS-1 Y612 and found no stimulation in UnAG-treated animals (Supplementary Fig.…”
Section: Unag Enhances Insulin Signaling and Glucose Uptakementioning
confidence: 99%
“…In this report, we have presented a transcriptional mechanism whereby carrageenan exposure leads to increased mRNA expression of GRB10 by GATA2 activation of the GRB10 promoter, with attention to Ser 307 of IRS1. Multiple sites of serine/threonine phosphorylation of IRS1 have been identified (39) and might also participate in the cascade of reactions described in this report but have not yet been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…These reactions lead to increased nuclear GATA2 and transcriptional activation of GRB10, which feeds back to inhibit Tyr(P)-IRS1. These interactions provide mechanistic links between the increase in Ser(P) 307 -IRS1 and the decline in Tyr(P)-IRS1 and help to clarify the relationship between Ser(P) 307 -IRS1 and Tyr(P)-IRS1 (39). Phosphorylations of IRS1 and their impact on the regulation of insulin sensitivity and propagation of insulin signaling have been considered in detail (39 -42).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, S6K1 participates in insulinmediated cell growth but-like mTORC1-also operates negative feedback loops at various levels of regulation. For example, several studies have shown that both mTORC1 and/or S6K1 phosphorylate specific serine residues on IRS proteins [6,7]. Moreover, some of these IRS-1 sites, notably Ser 1101 and Ser 636, were differentially regulated by mTOR and S6K1 [8,9].…”
Section: Introductionmentioning
confidence: 99%